2015
DOI: 10.1016/j.jval.2015.09.1927
|View full text |Cite
|
Sign up to set email alerts
|

Public Health And Economic Impact of A Quadrivalent Influenza Vaccine In Comparison to The Trivalent Influenza Vaccine In Brazil Over The Period Of 2010 – 2013

Abstract: Objectives: To estimate long-term clinical outcomes of using rilpivirine/tenofovir/emtricitabine (single tablet regimen) in treatment of naïve patients with HIV-1 RNA< 100 000 copies/ml in the Russian Federation. MethOds: The mathematical model was developed in Microsoft Office 2013. The time horizon was 5 years. The model included two submodels: Markov's model and tree-decision model. The following outcome measures were used in present study: Number of deaths, Years of life lost, Number of hospitalizations. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“… 8 The CDC model was adapted and used to assess the cost of switching from trivalent to quadrivalent vaccines from a Brazilian healthcare and societal perspective from 2010 to 2013. 33 It was estimated that the use of quadrivalent instead of trivalent vaccine in Brazil would have reduced the number of influenza cases by 654,018, reduced the number of hospitalizations by 7536, and reduced influenza-related deaths by 1122. In 2013 when the rate of mismatch of IIV3 with the circulating influenza B strain was >90%, the model showed that quadrivalent vaccine could have avoided influenza-related costs of R$ 1 million to the health system and R$ 62 million to society.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 8 The CDC model was adapted and used to assess the cost of switching from trivalent to quadrivalent vaccines from a Brazilian healthcare and societal perspective from 2010 to 2013. 33 It was estimated that the use of quadrivalent instead of trivalent vaccine in Brazil would have reduced the number of influenza cases by 654,018, reduced the number of hospitalizations by 7536, and reduced influenza-related deaths by 1122. In 2013 when the rate of mismatch of IIV3 with the circulating influenza B strain was >90%, the model showed that quadrivalent vaccine could have avoided influenza-related costs of R$ 1 million to the health system and R$ 62 million to society.…”
Section: Discussionmentioning
confidence: 99%
“…In 2013 when the rate of mismatch of IIV3 with the circulating influenza B strain was >90%, the model showed that quadrivalent vaccine could have avoided influenza-related costs of R$ 1 million to the health system and R$ 62 million to society. 33 …”
Section: Discussionmentioning
confidence: 99%